Sedimentological and dendrochronological indicators of coastal storm risk in western France. (July 2018) - Pouzet, Pierre; Robin, Marc; Decaulne, Armelle; Gruchet, Bastien; Maanan, Mohamed
Highlights: Dendrochronology detects storm events using a tree-ring disturbance analysis. Sedimentological indicators identify extreme events with marine flooding. Coupling the two proxies is a powerful tool to characterize coastal extreme events. Abstract: This paper compares results from two different environmental methods to observe past storm impacts: the back coastal barrier stratigraphical and dendrochronological archives. With a detailed historical database of the past 50 years storm observations, we discuss the combination of results from these two methods in a coastal study located in western France. The study shows that neither tree ring nor sedimentological results build a complete storm chronology by themselves. However, the combination of the two is sufficient to detect the strongest storms, which caused marine flooding. Comparing them with an accurate impact of storm chronology, extracted from written sources to test their robustness, we show that the combination of these two approaches offer a complete dataset. From this exhaustive historical sequence ranging from 1955 to 2016, three winters with major storms are highlighted in Traicts du Croisic: 1990, 1978 and 1972. Combining dendrochronology and sedimentology therefore enables a better understanding of extreme storm occurrences.